Early in-hospital exposure to statins and outcome after intracerebral haemorrhage – Results from the Virtual International Stroke Trials Archive. (March 2020) - Doerrfuss, Jakob I; Abdul-Rahim, Azmil H; Siegerink, Bob; Nolte, Christian H; Lees, Kennedy R; Endres, Matthias; Kasner, Scott E; Scheitz, Jan F
Abstract: Introduction: Recent data suggest that statin use after intracerebral haemorrhage might be beneficial. However, data on the effects of early in-hospital statin exposure are lacking. Therefore, we sought to assess whether (1) early statin exposure during the acute phase after intracerebral haemorrhage and (2) early continuation of prevalent statin use are associated with favourable functional outcome. Patients and methods: Data were obtained from the Virtual International Stroke Trials Archive. Patients were categorised according to use patterns of statins during this early in-hospital phase (continuation, discontinuation or new initiation of statins). Univariate and multivariable analyses were conducted to explore the association between early statin exposure and functional outcome. Results: A total of 919 patients were included in the analysis. Early in-hospital statin exposure (n = 89, 9.7%) was associated with better functional outcome (modified Rankin Scale ≤ 3) compared with 790 patients without statin exposure before or early after the event (66% versus 47%, adjusted OR 2.1, 95% confidence interval 1.3–3.6). Compared with patients without exposure to statins before and early after the event, early continuation of statin therapy (n = 57) was associated with favourable functional outcome (adjusted odds ratio 2.6, 95% confidence interval 1.3–5.2). The association between early continuation of statins and outcome remained robust in sensitivity analyses restricted to patients able to take oral medication within 72 h and one-week survivors. Discussion: It is possible that part of the observed associations are not due to a protective effect of statins but are confounded by indication bias. Conclusion: Statin exposure and continuation of prevalent statin therapy early after intracerebral haemorrhage are associated with favourable functional outcome after 90 days.